(untitled) (Al-Academy, 2020)
The peculiarity of worship spaces in the Islamic architecture is evident by its symbolic connotations with doctrinal connections, thus the niche has a major status in that symbolic connotation, which transformed due to the cultural interaction from a rock on the wall directed towards Mecca into an element of integrated structural entity with performative and aesthetic characteristics. The spread of the Islamic religion contributed to subjecting it to a design acculturation process, thus the problem of the research was raised by the following question: has the evolutionary tendency of acculturation been able to effect a major transformation in the niche design? The research aims at identifying the design acculturation and its translation methods of niche as a design text. The theoretical framework consists of two sections, the first addressed acculturation and its design translation and the second is the niche design acculturation. The research arrived at indicators that contributed to preparation of the intentional sample analysis form. The research adopted a comparative description approach to reach at a set of results and conclusions including that: the acculturation addresses the niche by design as a translatable text in different styles subject to the environmental data of all kinds and the personality of the designer, and it does not go beyond the standards of Islamic thought and the reason of constructing it as a substantial element of the prayer space. Keywords: acculturation, design, space, niche